High-strength-plastic multi-component alloy material for paper cutter
By adopting high-strength-plastic multi-component alloy materials, the shortcomings in strength, hardness and plasticity of existing paper cutting knife materials are solved, and the cost is reduced by avoiding heat treatment, so as to adapt to the shearing needs of papers of different hardness are achieved.
Patent Information
- Application Number
- CN202510107234.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
AI Technical Summary
The existing paper cutting knife materials have shortcomings in strength, hardness and plasticity, and require complex heat treatment processes, which are costly.
High-strength-plastic multi-component alloy material, whose composition is CraVbNbcZrdTie, is prepared by non-consumable vacuum arc smelting and electromagnetic stirring, forming a two-phase structure of BCC+Laves, avoiding heat treatment.
It achieves high strength, high hardness and low brittleness, adapts to the shearing needs of papers of different hardness, reduces production costs, and improves the composition stability of the material.
Smart Images

Figure CN119876729A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal alloys and preparation thereof, and in particular to a high-strength-plastic multi-component alloy material for paper cutters. Background Art
[0002] During the cutting process, the paper cutter needs higher strength, hardness and plasticity to maintain the stability and durability of the cutting. The different properties of different materials also affect its application range and cutting effect. Choosing the right material and structure can improve the service life and cutting accuracy of the paper cutter. At present, the alloy grades for paper cutters mainly include T10A, 9CrSi, W18Cr4V and so on. T10A is an ordinary carbon tool steel with high hardness, good mechanical properties and easy processing, but low strength. It is mostly used to make medium and low-grade paper cutter blades. 9CrSi is a carbon steel material with high hardness and high wear resistance. It is often used in the production of medium and high-grade paper cutter blades. W18Cr4V is a high-speed steel with high hardness, high wear resistance and high heat resistance. It is suitable for paper cutter blades with high hardness requirements, but it is more brittle. The performance guarantee of the three alloys requires complex heat treatment processes, which is expensive.
[0003] The traditional alloy system is mainly based on an element with some special properties, and a small amount of other elements is added to improve its performance. The types of commonly used metal elements are limited, and the amount of addition is also limited, which invisibly restricts the number of alloy materials that can be used. The concept of multi-component alloys (high entropy alloys) breaks this limitation, and the number of main elements is often ≥5. The reported high-performance multi-component alloys are often based on a system. By increasing or changing the content of one element, the microstructure of the alloy can be significantly changed to improve the performance. Multi-component alloys have a broad application space in the fields of aerospace, petrochemicals, molds, mechanical parts, etc. with their unique structure and properties. Developing an alloy material that can meet high strength, high hardness and low brittleness without heat treatment has great application potential in markets such as paper cutters. Summary of the invention
[0004] The object of the present invention is to provide a high-strength-plastic multi-component alloy material for paper cutters to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: A high-strength-plastic multi-component alloy material for paper cutters, the composition of which is designed according to the atomic ratio: Cr a V b Nb c Zr d Ti e, where a:b:c:d:e=(0.1-0.5):(0.3-0.7):(0.4-0.6):(0.8-1.2):(0.8-1.2).
[0006] Preferably, the chemical composition of the multi-component alloy system is designed according to the atomic ratio: Cr a V b Nb c Zr d Ti e ; Where a=0.1, b=0.5, c=0.5, d=1, e=1.
[0007] Preferably, the chemical composition of the multi-component alloy system is designed according to the atomic ratio: Cr a V b Nb c Zr d Ti e ; wherein a=0.3, b=0.5, c=0.5, d=1, e=1 A method for preparing a multi-component alloy material comprises the following steps:
[0008] S1. The titanium sponge block and the metal raw materials Cr, V, Nb, Zr, and Ti prepared according to the ratio are respectively placed in two different crucibles in a non-consumable vacuum arc melting furnace, the furnace chamber is first evacuated, and then backfilled with argon gas, and the titanium sponge block in one crucible is melted under the protection of argon gas to remove the residual oxygen in the melting environment and prevent oxidation of the metal during the melting process;
[0009] S2. Under argon protection, arc melting is performed on the alloy with good ratio in another crucible, and electromagnetic stirring is performed during the arc melting process. After cooling, a button sample is obtained; the button sample is turned over and the melting is repeated several times to ensure that the alloy material is completely melted and the composition is uniform;
[0010] S3. Take out the cooled sample from the melting furnace, cut it into suitable small pieces, remove the surface oxide scale of the small pieces, put the small pieces back into the arc melting furnace, melt, suck-cast and cool to obtain alloy samples of different sizes.
[0011] Preferably, the preparation in step S1 includes a process of cleaning the same;
[0012] The cleaning process is to grind the metal raw material with an angle grinder, a grinding wheel machine or sandpaper, and then use alcohol or acetone as a cleaning solvent to oscillate and clean the metal raw material in an ultrasonic wave for 5 to 10 minutes;
[0013] The power density of the ultrasonic wave is 0.5-1.5 W / cm 2 , frequency is 25~50Hz.
[0014] Preferably, in step S1, the furnace chamber is evacuated to a vacuum of 2.5×10 -3 After Pa, open the argon valve to restore the pressure in the furnace chamber to 1-20Pa;
[0015] The electric current of the arc melting is 50A-120A.
[0016] Preferably, in step S2, the button sample is turned over before repeating the arc melting process each time;
[0017] The arc melting process is repeated multiple times and the molten state needs to be maintained for 2 minutes to 5 minutes.
[0018] Preferably, the surface oxide scale is removed in step S3 by grinding the metal raw material with an angle grinder, a grinding wheel machine or sandpaper, and then the metal raw material is oscillated and cleaned in an ultrasonic wave for 5 to 10 minutes using alcohol or acetone as a cleaning solvent;
[0019] The power density of the ultrasonic wave is 0.5-1.5 W / cm 2 , frequency is 25~50Hz;
[0020] The vacuum suction casting pressure in step S3 is 1-10Pa.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention adjusts the Cr content to achieve the best combination of strength, hardness and plasticity to meet the shearing requirements of papers of different hardness. Its performance maintains the high hardness of existing paper cutter materials, and at the same time has obvious advantages over existing materials in major performance indicators such as yield strength and plasticity. The composition of the material is stable in the cast state and does not require heat treatment, thus saving a lot of heat treatment costs.
[0023] 2. The alloy material of the present invention has a simple BCC+Laves two-phase structure in the cast state, and Laves is a hard cubic C15 structure. As the Cr content increases, the Laves phase content increases and its strength increases. 0.1 V 0.5 Nb 0.5 Zr1Ti1 and Cr 0.3 V 0.5 Nb 0.5 The two alloys Zr1Ti1 have different strength-plasticity combinations and are suitable for cutting papers of different hardness. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the XRD spectrum of the Cr-V-Nb-Zr-Ti quinary alloy system prepared in Examples 1 and 2. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The following embodiment provides a high-strength-plastic multi-component alloy material for a paper cutter, wherein the composition is Cr a V 0.5 Nb 0.5 Zr1Ti1, where a is 0.1 and 0.3 respectively. The atomic percentage can be converted to atomic percentage and the corresponding calculation can be performed. For example, when a=0.1, the atomic percentage of Cr is (0.1 / 3.1)*100%.
[0027] Example 1
[0028] A high-strength-plastic multi-component alloy material for a paper cutter, comprising metal raw materials of the following atomic ratios: Cr0.1, V0.5, Nb 0.5, Zr 1, Ti 1, expressed as Cr 0.1 V 0.5 Nb 0.5 Zr1Ti1 multi-component alloy, referred to as Cr0.1.
[0029] The preparation method of the above Cr0.1 multi-component alloy is as follows:
[0030] (1) Prepare metal raw materials Cr, V, Nb, Zr, Ti and sponge titanium blocks, and use a grinder to remove surface impurities and oxides. The purity of each metal block is higher than 99.9wt%. After grinding, weigh according to the ratio, and use alcohol as the cleaning solvent. At a power density of 0.8W / cm 2 The mixture was cleaned in an ultrasonic cleaning machine with a frequency of 33 Hz for 5 minutes and dried for later use;
[0031] (2) The titanium sponge block and the metal raw materials Cr, V, Nb, Zr and Ti prepared according to the ratio are respectively placed in two different crucibles in a non-consumable vacuum arc melting furnace, and the vacuum is evacuated to 2.5×10 -3 Pa, then backfill with argon to 5Pa. Under the protection of argon, first melt the titanium sponge block for 1min, and then melt the weighed metal raw materials in another crucible at a current of 60A. The arc melting process is accompanied by electromagnetic stirring to increase the uniformity of alloy mixing. To ensure the uniform chemical composition of the alloy ingot, each metal ingot is turned over 5 times, and each melting time is 60s to obtain a button sample;
[0032] (3) The button sample is taken out, cut into suitable small pieces, and its surface oxide layer is removed. The button sample is placed in an arc melting furnace and step (2) is repeated (no additional flip melting is required). The Cr0.1 multi-component alloy rod is obtained by suction casting at a pressure of 5 Pa.
[0033] Example 2
[0034] A high-strength-plastic multi-component alloy material for a paper cutter, comprising metal raw materials of the following atomic ratios: Cr0.3, V0.5, Nb 0.5, Zr 1, Ti 1, expressed as Cr 0.3 V 0.5 Nb 0.5 Zr1Ti1 multi-component alloy, referred to as Cr0.3.
[0035] The preparation method of the above Cr0.3 multi-component alloy is as follows:
[0036] (1) Prepare metal raw materials Cr, V, Nb, Zr, Ti and sponge titanium blocks, and use a grinder to remove surface impurities and oxides. The purity of each metal block is higher than 99.9wt%. After grinding, weigh according to the ratio, and use acetone as the cleaning solvent. At a power density of 0.8W / cm 2 The mixture was cleaned in an ultrasonic cleaning machine with a frequency of 33 Hz for 5 minutes and dried for later use;
[0037] (2) The titanium sponge block and the metal raw materials Cr, V, Nb, Zr and Ti prepared according to the ratio are respectively placed in two different crucibles in a non-consumable vacuum arc melting furnace, and the vacuum is evacuated to 2.5×10 -3 Pa, then backfill with argon to 5Pa. Under the protection of argon, first melt the titanium sponge block for 1min, and then melt the weighed metal raw materials in another crucible at a current of 70A. The arc melting process is accompanied by electromagnetic stirring to increase the uniformity of alloy mixing. To ensure the uniform chemical composition of the alloy ingot, each metal ingot is turned over 5 times, and each melting time is 60s to obtain a button sample;
[0038] (3) The button sample is taken out, cut into suitable small pieces, and its surface oxide layer is removed. The button sample is placed in an arc melting furnace and step (2) is repeated (no additional flip melting is required). The Cr0.2 multi-component alloy rod is obtained by melting and casting at a pressure of 10 Pa.
[0039] The Cr in Examples 1 and 2 was analyzed by X-ray diffractometer. x V 0.5 Nb 0.5 Phase analysis of ZrTi (x = 0.1, 0.3) was performed with an operating voltage and current of 40 KV and 20 mA respectively, an X-ray source of CuKα (λ = 0.1542 nm) rays, and a scanning angle 2θ ranging from 20 to 100°.
[0040] The XRD spectra of the alloys of Examples 1 and 2 are as follows: Figure 1 As shown by Figure 1 It can be seen that Cr 0.1 The alloy phase composition is BCC and a small amount of Laves structure phase. 0.5 Nb 0.5 The BCC single-phase solid solution structure of ZrTi, the addition of Cr element leads to the formation of Laves phase in the alloy. 0.3 Alloy phase composition comparison Cr 0.1 There is no change, it is still BCC+Laves phase, but the diffraction peaks of the alloy Laves structure phase increase, indicating that the increase of Cr element leads to the precipitation of Laver phase.
[0041] Using Cr-free V 0.5 Nb 0.5 ZrTi multi-component alloy is used as comparative example 1 of the present application. Three common alloys for coating scrapers, 316 stainless steel, Ti-6Al-4V, and WC-Co alloy, are selected as comparative examples 2, 3, and 4, respectively. Hardness tests and compression energy tests are performed on Examples 1, 2, and comparative examples 1 to 4. The test data are shown in Table 1.
[0042] Hardness test method: HVS-1000B Vickers microhardness tester was used, with a loading load of 200g and a loading time of 15s. In order to reduce experimental errors and ensure the accuracy of the data, 10 points were selected for each alloy, the maximum and minimum values were removed, and the average value of the remaining hardness was taken as the microhardness value of the alloy.
[0043] Compression performance test method: The diameter of the cylindrical specimen used for the compression test is 4 mm and the height is 6 mm. The axis of the specimen is parallel to the outer surface of the cylinder, and the upper and lower planes are parallel. The compression test is carried out at room temperature using a computer-controlled high-temperature electronic universal testing machine. Apply 5.6×10 -3 A constant compression speed of mm / s corresponds to 10 -3 s -1 The initial strain rate.
[0044] Table 1 Performance data of embodiments and comparative examples
[0045] Yield strength(MPa) Plasticity(%) Hardness (HV) Example 1 1100 40 470 Example 2 1330 8 630 Comparative Example 1 832 18.6 350 Comparative Example 2 600-900 5-10 150-200 Comparative Example 3 500-700 10-15 350-400 Comparative Example 4 900-1200 2-5 >1000
[0046] As can be seen from Table 1, the yield strength of Examples 1 and 2 is significantly improved compared with Comparative Example 1 as the Cr element increases. At the same time, they also have obvious advantages over Comparative Examples 2 and 3, and are close to Comparative Example 4. At the same time, they are much ahead of Comparative Example 4 in plasticity. As the Cr content increases, the strength of the embodiments is further improved, but at the expense of a decrease in plasticity. Among them, the yield strength of Example 1 is 1100MPa, the plastic strain is 40%, and the hardness is 470HV. It has a good combination of strength, hardness and plasticity, and has obvious advantages over Comparative Examples 1, 2, and 3. The advantage of Comparative Example 4 is high strength and hardness, but it is brittle. Example 2 surpasses Comparative Example 4 in strength and is improved in plasticity.
[0047] With the difference in the content of an element, there are differences in the phase structure of the multi-component alloy, which ultimately leads to differences in performance. By adding different Cr contents, the applicant has reason to infer that the optimal combination of strength and plasticity can be achieved by regulating the content of the Cr element to meet the shearing requirements of papers of different hardness. Its main indicators have obvious advantages over existing materials. After annealing, the two embodiments of the present invention do not change in composition, and the strength and plasticity are not greatly improved. They can be used directly in the cast state without the need for heat treatment process, saving a lot of heat treatment costs.
[0048] The present invention provides a high-strength and high-hardness multi-component alloy material for paper cutters and a preparation method thereof, which provides useful inspiration for how to control the generated phase by changing the alloy elements, thereby improving and regulating the alloy properties. The preparation method of the present invention is simple and reliable, the selected elements are non-toxic and easy to obtain, the alloy has obvious advantages over medium, low and high-end paper cutters in terms of performance, and has good economy and high application value.
[0049] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.
Claims
1. A high-strength-plastic multi-component alloy material for a paper cutter, characterized in that: Its composition is designed according to the atomic ratio: Cr a V b Nb c Zr d Ti e , where a:b:c:d:e=(0.1-0.5):(0.3-0.7):(0.4-0.6):(0.8-1.2):(0.8-1.2).
2. The high-strength-plastic multi-component alloy material for paper cutters according to claim 1, characterized in that: The chemical composition of the multi-component alloy system is designed according to the atomic ratio: Cr a V b Nb c Zr d Ti e ; Where a=0.1, b=0.5, c=0.5, d=1, e=1.
3. The high-strength-plastic multi-component alloy material for paper cutters according to claim 1, characterized in that: The chemical composition of the multi-component alloy system is designed according to the atomic ratio: Cr a V b Nb c Zr d Ti e ; where a=0.3, b=0.5, c=0.5, d=1, e=1.
4. A method for preparing the multi-component alloy material according to claims 1-3, characterized in that: The steps include: S1. The titanium sponge block and the metal raw materials Cr, V, Nb, Zr, and Ti prepared according to the ratio are respectively placed in two different crucibles in a non-consumable vacuum arc melting furnace, the furnace chamber is first evacuated, and then backfilled with argon gas, and the titanium sponge block in one crucible is melted under the protection of argon gas to remove the residual oxygen in the melting environment and prevent oxidation of the metal during the melting process; S2. Under argon protection, arc melting is performed on the alloy with good ratio in another crucible, and electromagnetic stirring is performed during the arc melting process. After cooling, a button sample is obtained; the button sample is turned over and the melting is repeated several times to ensure that the alloy material is completely melted and the composition is uniform; S3. Take out the cooled sample from the melting furnace, cut it into suitable small pieces, remove the surface oxide scale of the small pieces, put the small pieces back into the arc melting furnace, melt, suck-cast and cool to obtain alloy samples of different sizes.
5. The method for preparing a multi-component alloy material according to claim 4, characterized in that: The preparation in step S1 includes a process of cleaning the same; The cleaning process is to grind the metal raw material with an angle grinder, a grinding wheel machine or sandpaper, and then use alcohol or acetone as a cleaning solvent to oscillate and clean the metal raw material in an ultrasonic wave for 5 to 10 minutes; The power density of the ultrasonic wave is 0.5-1.5 W / cm 2 , frequency is 25~50Hz.
6. The method for preparing a multi-component alloy material according to claim 4, characterized in that: In step S1, the furnace chamber is evacuated to a vacuum of 2.5×10 -3 After Pa, open the argon valve to restore the pressure in the furnace chamber to 1-20Pa; The electric current of the arc melting is 50A-120A.
7. The method for preparing a multi-component alloy material according to claim 4, characterized in that: In step S2, the button sample is turned over before repeating the arc melting process each time; The arc melting process is repeated multiple times and the molten state needs to be maintained for 2 minutes to 5 minutes.
8. The method for preparing a multi-component alloy material according to claim 4, characterized in that: In step S3, the surface oxide scale is removed by grinding the metal raw material with an angle grinder, a grinding wheel machine or sandpaper, and then the metal raw material is oscillated and cleaned in an ultrasonic wave for 5 to 10 minutes using alcohol or acetone as a cleaning solvent; The power density of the ultrasonic wave is 0.5-1.5 W / cm 2 , frequency is 25~50Hz; The vacuum suction casting pressure in step S3 is 1-10Pa.